Equity Market Timing Approach in IPO and Rights Issue of Companies in Indonesia - Wihandaru Sotya Pamungkas; Tulus Haryono; Djuminah Djuminah; Bandi Bandi; Doddy Setiawan (Journal of Accounting and Investment, 2019)
The aim of this study is to analyse the effect of equity market timing on the issuance of new shares and capital structures in companies, excluding those in the financial sector, that conducted Initial Public Offerings (IPOs) and rights issues (RIs) in Indonesia from 1990 to 2014. The study took a sample of companies with less than 100% leverage that had experienced delisting and relisting. The results were obtained at the time of an IPO (i.e. the time of a new shares issuance through go public), RI (the time of a new shares issuance as a rights issue), and RI+1 (one year after the rights issue) and capital structure. There was an effect of equity market timing on the issuance of new shares at IPO+1 (1 year after the IPO), IPO+2, RI+2, RI+3 and RI+4, but the companies issued a small number of new shares and raised the funds they lacked by issuing new debt to obtain an optimal capital structure. These results add to the findings that the market timing theory and trade-off theory are not mutually exclusive.